Amplification and sequence of spacer region between two tRNA genes and its flanking region in the chloplast genome of centella asiatica L. - Manju Elizabeth P (Department of Plant Biotechnology, College of Agriculture, 2006)
The study entitled “Amplification and sequencing of spacer region between two tRNA genes and its flanking region in the chloroplast genome of Centella asiatica L.” was conducted at the Department of Plant Biotechnology, College of Agriculture, Vellayani, Thiruvananthapuram during 2005-2006 with the objective of isolating a spacer region and its flanking regions from the chloroplast genome of Centella asiatica to develop a species specific vector for the chloroplast transformation.